A fundamental in situ IR spectroelectrochemical study of the electrical polarization of nickel, copper and gold electrodes in the presence of the unstable tellurocyanate ion in DMSO and DMF solutions. Issue 40 (7th May 2015) - Alwis, Kethsiri H. K. L.; Mucalo, Michael R.; Lane, Joseph R.
<x xml:space="preserve">Abstract</x> TeCN− ions sense via decomposition the presence of dissolved metal ions produced by electrodissolution of Ni, Cu and Au electrodes.